The validity of measuring skipping cadence with a novel wearable sensor - SINTEC smart patch - Verdel, N.; Drobnic, M.; Maslik, J.; Hellman, O.; Gumiero, A.; Dellatorre, L.; Holmberg, H. C.; Hjort, K.; Supej, M. (ISBS Proceedings Archive (Michigan), 2022)
The aim of this study was to test the validity of running cadence assessed with a novel smart patch designed within a SINTEC Horizon 2020 project. Participants performed 3 consecutive 20-seconds skipping with increasing intensity (slow, medium, fast). Cadence was derived from raw data from a "SINTEC" smart patch, Dytran accelerometers, and HBM bilateral force plates. Data from all devices were compared using Bland-Altman analysis and Wilcoxon signed-rank test. The mean bias between cadence measured with Dytran accelerometer and force plates with ``SINTEC`` smart patch was 0.08 and -0.17 steps/min, respectively. In addition, there were no statistically significant difference between the mean cadence determined with different sensors/devices. Therefore, we can conclude that the measurement of cadence using a novel SINTEC smart patch showed good validity.